Individual Investors – Are they Emotionally Biased? - Joshi, Dr. C. S.; Badola, Ms. Sneha (The journal of contemporary issues in business and government, 2022)
The stock market is a crucial aspect of not just India’s financial market but of the world’s economy as a whole, as it results into massive investments performances. In the fast-moving financial scenario, the traditional finance is unable to explain the irrationality of an individual investor, as they are irrational and influenced by irregularities in financial market. Behavioural finance has earned a lot of significance through its attempts to discover such causes which are behind an investor’s behaviour. The objective of this research paper is to investigate the key impact of behavioural biases in the investment decision making of individual investors. The study consisted of 378 individual investors trading in Indian stock exchanges and data was collected through a questionnaire developed for the purpose of research. The questionnaire was empirically tested after approving its reliability and validity. It is interesting to know the impact of different emotional biases affecting the investment decisions of individual investors. Loss aversion bias, Status quo bias and Optimism bias were studied.